Capita Selecta: Horizons of Islamic Education, Curriculum Issues, and Classical to Contemporary Learning - Zulkifli, Zulkifli; AM, Rusydi; Karim, Shofwan; Suriadi, Hari (Jurnal Kajian dan Pengembangan Umat, 2025)
This study analyses the development and transformation of Islamic education curricula from the classical era to the contemporary period, focusing on changes in systems, teaching methods, and the challenges encountered. Using a historical-comparative analytical approach, the research examines the evolution of Islamic education curricula, starting from mosque-based learning systems in the classical era, the development of madrasas in the mediaeval period, to the adoption of digital technology and modern teaching methods in the contemporary era. The findings reveal that the Islamic education curriculum has undergone significant transformations to respond to the needs of the times. It evolved from an initial focus on Quranic studies and religious sciences to a system integrating religious and general knowledge, and further to the adoption of technology and innovative teaching methods in the Society 5.0 era. Key challenges identified include balancing fundamental Islamic values with the demands of modernity, integrating technology into learning, and fostering 21st-century competencies. This study recommends developing a holistic curriculum that integrates Islamic values with technological innovations and global needs while emphasising character development and soft skills to prepare an excellent Muslim generation for the digital age.